Clinical and microbiological features of Bartholin's gland abscess in pregnant and non-pregnant women. (3rd April 2021) - Grinberg, Noa; Rotem, Reut; Diamant, Hagit; Barg, Moshe; Sheizaf, Boaz; Yohai, David; Weintraub, Adi Y.
Abstract: Objective: The data regarding microbiological and clinical characteristics of Bartholin gland abscesses during pregnancy is limited. Given the hormonal and physiological changes during pregnancy we aimed to examine whether a difference exists in the clinical and microbiological features of Bartholin's gland abscess during pregnancy and the puerperium as compared with nonpregnant patients. In addition, we aim to evaluate whether a Bartholin's gland abscess during pregnancy is associated with adverse pregnancy outcomes. Study design: A retrospective cohort study was conducted, including all women with Bartholin's gland abscess who were treated surgically between the years 2009–2016 in the Soroka University Medical Center. Various demographic, clinical and microbiological characteristics were retrieved and a comparison was made between patients with a Bartholin's gland abscess during pregnancy and the puerperium (study group) as compared with nonpregnant patients (controls). In addition, obstetrical characteristics of patients in the study group were retrieved. Results: Of the 363 women who were treated surgically, 38 (10.5%) were in the study group. Women in the study group were significantly younger (26.8 versus 32.8 p < .001). No differences were found between the groups with regard to the clinical presentation (affected side, fever, leukocytosis and need for antimicrobial treatment) or the selected mode of drainage. In addition, no difference was found in the percentage of positive culture results, nor in the distribution of the pathogens between the groups, in both groups the most common pathogen was Escherichia coli . Yet, among the study group, recurrence of the abscess was more common (13.5 versus 2.15% p = −.067) as evident by significantly higher recurrent referrals to the emergency department and recurrent hospitalizations (28.9 versus 14.8%, p < .05, and 26.3 versus 8.0% p < .001, respectively). Of note, fever after the procedures, pain, discharge and bleeding did not differ significantly between groups. No cases of premature rupture of membranes or chorioamnionitis were noted following treatment. Conclusions: In our cohort, no differences were found between the study groups in the clinical presentation and microbiological features. A significantly higher recurrence rate was noted in the study group. Among pregnant patients no adverse perinatal outcomes were noted.